THE EFFECT OF STAD TYPE COOPERATIVE LEARNING MODEL ASSISTED BY POWER POINT MEDIA ON STUDENT LEARNING OUTCOMES ON THE SUBJECT MATTER OF TEMPERATURE AND HEAT TEMPERATURE AND HEAT - Siagian, Maria Agnes; Siregar, Nurdin (UNIVERSITAS NEGERI MEDAN, 2024)
The selection of an inappropriate model and the lack of use of learning media cause low student learning outcomes. This study aims to determine the effect of STAD type cooperative learning model assisted by power point media on the subject matter of temperature and heat. The type of this research is quasi experiment. The population in this study were all students of class XI SMA Negeri 1 Percut Sei Tuan. Sampling was done by simple random sampling technique consisting of two classes, namely class XI-Matlanfor as the experimental class and class XI-Matlansos as the control class, each of which amounted to 33 people. The instrument used was a student learning outcomes test totaling 20 questions in the form of multiple choice. The results of data analysis showed that the STAD type cooperative learning model assisted by power point media had a significant effect on student learning outcomes on temperature and heat material.